Analisis Sistem Akuntansi Penerimaan dan Pengeluaran Kas pada Madrasah Aliyah Nurul Islam Bayung Lencir - Anita Naning Wulandari; Efni Anita (Lembaga Yasin AlSys, 2026)
The implementation of technology-based accounting systems in educational institutions aims to enhance the transparency and accountability of financial management; however, studies that specifically examine the application of cash receipts and disbursements accounting systems in madrasah remain relatively limited. This study aimed to analyze the implementation of a technology-based cash receipts and disbursements accounting system and to identify the challenges faced by Madrasah Aliyah Nurul Islam Bayung Lencir in its financial management. A qualitative approach with a descriptive case study design was employed, involving informants consisting of the principal, treasurer, administrative staff, and teachers involved in financial management, who were selected through purposive sampling. Data were collected through in-depth interviews, direct observations, and analysis of the madrasah’s financial documents, and were analyzed using thematic analysis through the stages of data reduction, data display, and conclusion drawing. The results showed that the implementation of the technology-based accounting system at Madrasah Aliyah Nurul Islam Bayung Lencir has not yet run optimally, with key constraints including limited human resource competencies, insufficient training, inadequate technological infrastructure, and low system integration. These conditions have led to a high dependence on manual recording before data are entered into the digital system, which affects the efficiency and accuracy of financial reporting. These findings underscore the importance of strengthening internal policies, enhancing human resource competencies, and improving infrastructure support to achieve more transparent and accountable financial management in madrasahs.